Focusing of inhomogeneous polarized modes of a laser waveguide dielectric resonator - Degtyarev, A.; Dubinin, M.; Maslov, V.; Senyuta, V. (Radiofizika i èlektronika, 2020)
Subject and Purpose. In this paper, spatial power characteristics of laser beams with inhomogeneous spatial polarization are theoretically investigated depending on whether they have moderate or sharp focusing. The spotlight of the numerical simulation of laser beam focusing in the terahertz range is on the laser waveguide dielectric resonator modes coincident with waveguide eigenmodes. Symmetric and asymmetric modes with both spatially inhomogeneous azimuthal and radial polarizations and homogeneous linear polarization of the field are considered. Methods and Methodology. The study of the electric field components of laser radiation beams in their free space propagation employs Rayleigh-Sommerfeld integrals in nonparaxial approximation. The focusing lens action on the laser radiation is considered using the amplitude-phase correction function. The total intensity distributions of the resonator modes and their particular field components in the lens focal area are examined. Results. Wave beams with inhomogeneous spatial polarization of radiation are needed for meeting important fundamental and applied problems concerning terahertz electromagnetic wave interaction with matter and including diagnostics of material surface, thin films and biological objects, design and development of terahertz systems of information transmission and processing, terahertz communication systems, achievement of subwave resolution in terahertz tomography, etc. The literature on pulsed radiation beam focusing in the terahertz region is available, which cannot be said about continuous radiation beam focusing, data on the subject being practically absent. In the present work, physical features of moderate and sharp focusing of laser beams have been theoretically studied in the case of their excitation by modes of the resonator with a circular dielectric waveguide with different spatial polarizations of the field. The obtained results give a more in-depth view of the focusing features of terahertz laser beams. Conclusions. Physical features have been established for spatial power characteristics of radiation beams with different spatial polarizations of the field in the case of the excitation by modes of the laser cavity upon a circular dielectric waveguide in the terahertz range and with the regimes of moderate and sharp beam focusing in the free space considered.